Over-the-top bundled services in the Korean broadcasting and telecommunications market: Consumer preference analysis using a mixed logit model. (August 2021) - Kim, Seho; Lee, Changhee; Lee, Jongsu; Kim, Junghun
Highlights: This study analyzes consumer preferences for OTT bundled services in Korea. Bundling OTT services to expand pay-TV market share is not an effective strategy. OTT services and TV broadcasting services have a complementary relationship. Government regulations on M&As in the media market need a global perspective. Abstract: Platform service providers in Korea and worldwide have launched over-the-top (OTT) bundled services, which increase market competitiveness. Forecasting the market expansion strategies of these providers can thus shed light on their future actions and influence government policies. In this context, this is the first study to analyze consumer preferences for bundled pay-TV and OTT services. However, due to a lack of market data availability, we conducted a discrete choice experiment and analyzed the marginal utilities of attributes using a mixed logit model. The results demonstrate that consumers expect an additional discount for pay-TV services when bundled with OTT services and that the more bundled services they currently use, the less sensitive they are to the discount rate. Furthermore, we found that OTT and TV broadcasting services have a complementary, rather than a substitute, relationship. Finally, according to a simulation analysis for the Korean broadcasting market, bundling OTT services to expand the market share of pay-TV service providers was largely ineffective.